2014
DOI: 10.1007/s40273-014-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

When to Use Discrete Event Simulation (DES) for the Economic Evaluation of Health Technologies? A Review and Critique of the Costs and Benefits of DES

Abstract: Modelling in economic evaluation is an unavoidable fact of life. Cohort-based state transition models are most common, though discrete event simulation (DES) is increasingly being used to implement more complex model structures. The benefits of DES relate to the greater flexibility around the implementation and population of complex models, which may provide more accurate or valid estimates of the incremental costs and benefits of alternative health technologies. The costs of DES relate to the time and experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…The number of discrete health states included in the model could lead to a decision to use discrete event simulation. 35 If a simpler model structure is used that does not represent all potentially important HSUs, the potential effects of such omissions should be examined and discussed.…”
Section: Discrete Health States Versus Discrete Event Simulationmentioning
confidence: 99%
“…The number of discrete health states included in the model could lead to a decision to use discrete event simulation. 35 If a simpler model structure is used that does not represent all potentially important HSUs, the potential effects of such omissions should be examined and discussed.…”
Section: Discrete Health States Versus Discrete Event Simulationmentioning
confidence: 99%
“…The reasons for such a choice are three-fold: firstly, as in our study we focus on the validation of the model that is statistical/analytical in nature, where simulation is used mainly for conducting probabilistic sensitivity analyses, it is more relevant to review the literature focusing on validation of similar "non-simulation" models; secondly, the domain of simulation modeling within OR/MS is well known for its careful attention to detailed model validation ( Balci, 1989;Sargent, 2001Sargent, , 2013Whitner & Balci, 1989 ), often focusing on highly simulationspecific issues (e.g. visual walkthroughs, etc) that could be less relevant to "non-simulation" focused studies; and thirdly, as discussed by Brailsford and Vissers (2011 ), the domain of health care simulation modeling applications is expanding by the rate of up to 30 papers per day and conducting a comprehensive review of such a body of literature deserves its own special focus (such as in, e.g., ( Fone et al, 2003 ) and ( Karnon & Afzali, 2014 )) and would have been impossible within the scope of this study.…”
Section: Operational Validitymentioning
confidence: 99%
“…The use of DES is also gaining momentum within the field of HTA itself [12][13][14]. There has been a recent systematic review on the use of DES for HTA [15], which identified 42 relevant studies. However, they excluded the studies that modelled capacity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the few studies that were identified in our review [19,20,26,28], most HTA studies do not address the effects of constraints explicitly when developing a patient-level model [15]. The reviewed studies showed that DES is an effective tool to assess the effects of constraints, but given the small number of studies found in our review, there is a gap in understanding on how DES can be used for considering explicit constraints when performing RM in HTA.…”
mentioning
confidence: 97%